(untitled) (PHARMACON, 2022)
ABSTRACT Staphylococcus aureus is one of the bacteria that causes infection which must be treated with antibiotics. The use of therapy that is not in accordance with the dose can cause resistance. Another alternative that can be done to deal with this resistance is to use herbal ingredients as the basis for therapy. The fig plant has been known by the public as a useful medicinal plant. Both the leaves and fruit of the fig plant contain many secondary metabolic compounds that are good for health. This study aims to find an appropriate cream formulation based on natural ingredients and to develop fig leaf extract which has been analyzed for its benefits as an antibacterial that inhibits the growth of Staphylococcus aureus bacteria in the form of a cream preparation so that it is easy to use. This research is an experimental laboratory research using the modified agar diffusion method, Kirby and Baeur diffusion, by means of wells. The results of the antibacterial effectiveness test showed fig leaf extract cream (Ficus carica L.) with a concentration of 15% had a larger diameter of the inhibition zone against Staphylococcus aureus with an average diameter of 10 cm on each bacterial medium. Fig leaf extract cream (Ficus carica L.) with a concentration of 15% has a soft texture even though it is stored at room temperature, hot or cold temperatures, the pH of the preparation of fig leaf extract cream (Ficus carica L.) is in accordance with skin pH (Ph = 6 ) so that it can be applied to the skin, the dispersion of the preparation is better than the other concentrations, namely free 250 grams with a diameter of 6 cm, and good adhesion, which is 5 seconds. Keywords: Antibiotic-Resistant Bacteria, Green gedi, Bioactive compounds, Molecular docking. Â ABSTRAK Staphylococcus aures merupakan salah satu bakteri penyebab infeksi yang harus diterapi dengan antibiotik. Penggunaan terapi yang tidak sesuai dosis dapat menyebabkan terjadinya resistensi. Adapun alternatif lain yang dapat dilakukan untuk menangani reseistensi tersebut ialah dengan menggunakan bahan herbal sebagai bahan dasar terapi. Tanaman ara sudah dikenal oleh masyarakat sebagai tanaman obat yang bermanfaat. Baik daun dan buah tanaman ara mengandung banyak senyawa metabolic sekunder yang baik bagi kesehatan. Penelitian ini bertujuan untuk menemukan suatu formulasi krim yang tepat berbasis bahan alam dan mengembangkan ekstrak daun ara yang telah dianalisis manfaatnya sebagai antibakteri yang menghambat pertumbuhan bakteri Staphylococcus aures dalam bentuk sediaan krim sehingga memudahkan dalam penggunaannya. Penelitian merupakan penelitian eksperimental laboratorium dengan metode difusi agar, difusi Kirby dan baeur yang dimodifikasi, dengan cara sumuran. Hasil pengujian efektivitas antibakteri menunjukkan krim ekstrak daun ara (Ficus carica L.) dengan konsentrasi 15% memiliki diameter zona hambat terhadap bakteri Staphylococcus aureus yang lebih besar dengan rata-rata diameter 10 cm pada setiap media bakteri. Krim ekstrak daun ara (Ficus carica L.) dengan konsentrasi 15% memiliki tekstur yang lembut meskipun disimpan dalam suhu ruang, suhu panas maupun suhu dingin, pH sediaan krim ekstrak daun ara (Ficus carica L.) sesuai dengan pH kulit (Ph = 6) sehingga dapat diaplikasikan untuk kulit, daya sebar sediaan lebih baik dibandingkan dengan konsentrasi yang lain yaitu bebas 250 gram dengan diameter 6 cm, serta daya lekat yang baik yaitu 5 detik. Kata kunci: Staphylococcus aures, Daun ara, Efektivitas antibakteri, Krim ekstrak daun ara.